Improving Learning Outcomes in Science Using Group Study Learning Method of SDN Kebon Kelapa Grade IV Students - Prayekti, Dr.; Rasyid, Dra. Rasyimah (IJRDO- Journal of Educational Research, 2017)
Kebon Kelapa Public Elementary School (hitherto Sekolah Dasar Negeri or SDN Kebon Kelapa) was favourably founded by the city government of Jakarta. Based on direct school observations both inside and outside of the classroom, there was a strong inclination that some students, either during the teaching learning period or break time, were always divided in groups. This phenomenon provided some obstacles in learning since it was hard, especially during lesson time, for the students to interact one another. Thus, the overall learning was seen to be passive and this further influenced their learning achievement especially that in Science subject where there was only 45% of the students who passed the minimum passing grade (or KKM) of 65. Therefore, an initiative to answer this challenge to improve the Grade IV students’ learning achievement in Science was then completed through conducting a comprehensive set of class action research. Preliminary data statistics showed that the average score was 42.26 and there were 20 students (64.52%) who were failed in this subject. In the first cycle, some improvements on the students’ scores were already indicated, as the average score was raised to 56.13. 19 students (61.29%) passed the KKM, while those achieving scores below the KKM were as many as 12 students (38.71%). Interestingly, in the second cycle of the strategy implementation, all the students (100%) profoundly passed the KKM with an average score of 96.13.